PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS LABORATORIUM DAN PENGARUHNYA TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK SMA NEGERI 8 MATARAM - Nevi Ernita; Ahmad Harjono; Nyoman Sridana (Lensa: Jurnal Kependidikan Fisika, 2013)
This study aims to determine: (1) The effect of guided inquiry learning model based on real laboratory and virtual laboratory on students' cognitive learning outcomes; (2) Effects of guided inquiry learning model based on real laboratory and virtual laboratory on students' psychomotor learning outcomes. The study sample consisted of the first experimental class of 34 students and the second class of 33 students. This research used randomized post-test control group design. Data were analyzed using independent sample t-test statistic technique with SPSS 19 for windows. The result of statistical analysis at 5% significant level shows: (1) the t-test value for the cognitive domain of -2.407 at sig.0.019; (2) the t-test value for the psychomotor domain is -5.595 on the sig. 0.00. However it can be concluded: (1) There is a significant difference in the cognitive learning outcomes of physics learners using guided inquiry based inquiry model based on real laboratory and virtual lab; (2) there is a significant difference in psychomotor learning result of physics learners using guided inquiry model based on real laboratory and virtual lab.